THE EFFECT OF USING PICTURE WORD INDUCTIVE MODEL ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Indah C.R Marbun and Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study aims to find out whether students’ achievement trough using Picture Word Inductive Model is higher than trough lecture method in writing procedure text. The research was conducted by experimental research used in two groups. They are experimental use picture word inductive model and control use lecture method. The subject of this were the students of SMP 32 class IX-A and IX-B consisted of 30 students for each class. To collecting the data was taken from writing test. After analyzing the data, it was found that the value of t-obs was 4.16 with degree of freedom (df) = 58 at the level of significance p(0,05) = 2,000. It means that t-obs is higher than t-table. It was found that teaching procedure text by use picture word inductive model is higher than lecture method. Picture word inductive model has a significant effect on students’ achievement in writing procedure text.